Recent developments in the understanding of the interactions between the vestibular system, memory, the hippocampus, and the striatum - Paul F. Smith; Paul F. Smith (Frontiers in Neurology, 2022)
Over the last two decades, evidence has accumulated to demonstrate that the vestibular system has extensive connections with areas of the brain related to spatial memory, such as the hippocampus, and also that it has significant interactions with areas associated with voluntary motor control, such as the striatum in the basal ganglia. In fact, these functions are far from separate and it is believed that interactions between the striatum and hippocampus are important for memory processing. The data relating to vestibular-hippocampal-striatal interactions have considerable implications for the understanding and treatment of Alzheimer's Disease and Parkinson's Disease, in addition to other neurological disorders. However, evidence is accumulating rapidly, and it is difficult to keep up with the latest developments in these and related areas. The aim of this review is to summarize and critically evaluate the relevant evidence that has been published over the last 2 years (i.e., since 2021), in order to identify emerging themes in this research area.